2010
DOI: 10.1002/ejlt.200900186
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitation of fish oil fatty acids and their ethyl esters by FT‐NIR models

Abstract: Consumption of fish oil and dietary supplements containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) has steadily increased because of their reported health benefits. A rapid procedure based on Fourier Transform Near Infrared Spectroscopy (FT-NIR) models was developed for analysis of fish oil and their ethyl ester derivatives to replace the time consuming GC method. Inclusion of fish oil or ethyl esters containing varied concentrations of OA, EPA, and DHA into the FT-NIR classification models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Many of the unsaturated FA with one or more trans double bonds coelute with their all-cis isomers when separated on PEG-coated columns [10], which could lead to overestimation of the all-cis LC n-3 PUFA content of fish products. This observation was recently confirmed when Fourier transform near-infrared (FT-NIR) spectroscopy was evaluated as an alternative method for LC n-3 PUFA determination [20]. FT-NIR quantification based on calibrated data acquired with a PEG column overestimated the amount of the all-cis LC n-3 PUFA compared with FT-NIR quantification based on calibration data obtained by use of a 100-m highly polar CPS column.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Many of the unsaturated FA with one or more trans double bonds coelute with their all-cis isomers when separated on PEG-coated columns [10], which could lead to overestimation of the all-cis LC n-3 PUFA content of fish products. This observation was recently confirmed when Fourier transform near-infrared (FT-NIR) spectroscopy was evaluated as an alternative method for LC n-3 PUFA determination [20]. FT-NIR quantification based on calibrated data acquired with a PEG column overestimated the amount of the all-cis LC n-3 PUFA compared with FT-NIR quantification based on calibration data obtained by use of a 100-m highly polar CPS column.…”
Section: Introductionmentioning
confidence: 83%
“…This would explain why Sébédio et al [11] found only geometric isomers of LC highly unsaturated PUFA in deep fried mackerel by use of a 30-m Supelcowax-10 column, the same GC column we used. We recently evaluated FT-NIR for quantification of FA in fish oil preparations enriched with EPA and DHA [20]. We observed that the amount of the all-cis highly unsaturated FA contained in these oils was significantly overestimated when a 30-m PEG FAMEWAX column was used for calibration of the FT-NIR spectrometer, rather than when a 100-m CP Sil 88 column was used.…”
Section: Discussionmentioning
confidence: 99%
“…Six replicate absorption spectra were measured for each test portion. These spectra were subsequently used to generate an average spectrum and in the development of PLS1 calibration models for the determination of FT-NIR index values, FA composition [28][29][30], and adulterant type and concentration in spiked EVOO samples. Various pre-processing steps were carried out as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The previously developed PLS1 calibration models to determine the FA composition of oils were based on observed FT-NIR spectra and used accurate GC determinations as primary reference [28][29][30]. All FA calibration models were updated and optimized for the determination of FA markers in EVOO.…”
Section: Development Of Pls1 Calibration Models For Rapid Determinatimentioning
confidence: 99%
See 1 more Smart Citation